(untitled) (Global Journal of Management and Business Research, 2019)
This paper aims to investigate the determinants of productivity growth in the Tunisian economy context over the period 1976 to 2010. Our theoretical model incorporates as key variables, domestic innovation, human capital, distance to technology frontier and external technology spillovers through import of high-tech products and foreign direct investments. Empirical results identify that the impact of domestic R